2000
DOI: 10.1143/jjap.39.3371
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Tantalum-Based Josephson Junction for an X-Ray Detector

Abstract: We evaluate the performance of a single flux quantum (SFQ) circuit and discuss its possible system-level application. First, we describe an optical-electrical-SFQ hybrid router system that is divided into three functions: an SFQ packet-routing function, a control function, and an optical transmission function. For the packet-switching core, we have developed a packet-switching architecture based on an internal speedup time-shifted Batcher Banyan approach. Our simulated results show that this architecture shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These workers reported energy resolutions at 5.9 keV of 41, 58, 65 and 129 eV for devices with dimensions of 20620, 1006100, 2006200 and 5006500 mm 2 , respectively. Morohashi et al 28 reported the fabrication of a tantalum-based STJ, which was designed for its greater stopping power for higher energy X-rays. An improved internal method for suppressing background current was reported by Nakagawa et al, 29 who used a micro-machined microstrip coil rather than a conventional external electromagnet.…”
Section: Detectorsmentioning
confidence: 99%
“…These workers reported energy resolutions at 5.9 keV of 41, 58, 65 and 129 eV for devices with dimensions of 20620, 1006100, 2006200 and 5006500 mm 2 , respectively. Morohashi et al 28 reported the fabrication of a tantalum-based STJ, which was designed for its greater stopping power for higher energy X-rays. An improved internal method for suppressing background current was reported by Nakagawa et al, 29 who used a micro-machined microstrip coil rather than a conventional external electromagnet.…”
Section: Detectorsmentioning
confidence: 99%